Hard Carbon Anodes and Novel Electrolytes for Long‐Cycle‐Life Room Temperature Sodium‐Sulfur Full Cell Batteries. Issue 6 (14th January 2016) - Kohl, M.; Borrmann, F.; Althues, H.; Kaskel, S.
Abstract : A novel combination of hard carbon anode sodium pre‐loading and a tailored electrolyte is used to prepare room temperature sodium‐sulfur full cell batteries. The electrochemical loading with sodium ions is realized in a specific mixture of diethyl carbonate, ethylene carbonate, and fluoroethylene carbonate electrolyte in order to create a first solid electrolyte interface (SEI) on the anode surface. Combining such anodes with a porous carbon/sulfur composite cathode results in full cells with a significantly decreased polysulfide shuttle when compared to half cells combined with metallic sodium anodes. Further optimization involves the use of Na2 S/P2 S5 doped tetraethylene glycol dimethyl ether based electrolyte in the full cell for the formation of a second SEI, reducing polysulfide shuttle even further. More importantly, the electrochemical discharge processes in the cell are improved by adding this dissolved complexation agent to the electrolyte. As a result of this combination sodium‐sulfur cells with tailored cathode materials and electrolytes can achieve high discharge capacities up to 980 mAh g −1 sulfur and 1000 cycles with 200 mAh g −1 sulfur remaining capacity, at room temperature. Abstract : A unique combination of the presodiation of hard carbon anodes, in a tailored NaPF6, diethyl carbonate, ethylene carbonate, and fluoroethylene carbonate containing an electrolyte, and the use of an Na2 S/P2 S5 doped tetraethylene glycol dimethyl ether electrolyte in subsequent full cells, leads to stable sodium‐sulfur batteries operable at room temperature with discharge capacities up to 980 mAh g −1 sulfur and 1000 reversible cycles.